Floristic study of weeds in watermelon crops in Savannah of Roraima, Brazil - Alves Albuquerque, José de Anchieta (2017)
The municipality of Bonfim is the second largest watermelon producer in the state and the incidence of weeds is as one of the factors that most affect the quality and crop productivity. The objective of this work was to study floristically weeds in watermelon crops in the municipality of Bonfim, in Roraimense savannah. The survey was conducted in 10 properties with an area of around 40 ha commercial planting watermelon. To collect the weeds used a square cast iron with dimensions of 0.50 x 0.50 m, being released randomly in the area. They were identified to genus, species, family and botany class. the phytosociological parameters were calculated: frequency, density, abundance, relative frequency, relative density, relative abundance and relative importance value index. There were also evaluated the life cycle, growth habit, propagation method and the photosynthetic pathway of invasive species. The composition of the infesting weed community in the raised area was considered heterogeneous, with 17 species in 10 plant families. Families with higher incidence were Poaceae and Fabaceae. The Digitaria and Sida genres had the highest number of species. Most of the identified weed spreads only by seed have annual life cycle and the C3 photosynthetic pathway.